Storage of wheat at high moisture - Ruska, Laslo; Timar, Adrian (Acta Agraria Debreceniensis, 2010)
Deterioration rates were determined for 15-19% moisture content wheat (Dropia cultivar) stored at constant temperatures. Deterioration rates were determined by measuring germination capacity of the grain and respiration rates of grain. Safe storage time was defined as the time for germination to decrease to 90%. Safe storage times of 19% m.c. wheat stored at constant temperatures ranged from 2.5 d at 30 and 35°C to 37 d at 10°C. Deterioration rates of 19% m.c. wheat stored with a step decrease in storage temperatures (35-25, 30-20, 25-20, and 20-15°C) were determined and safe storage times were satisfactorily predicted. Safe storage times of 17% m.c. wheat were 5, 7, and 15 d at 35, 30, and 25°C, respectively. Respiration rates and germination percentages of 15 and 16% m.c. wheat stored at 25°C remained constant for 70 d. The respiration rates of 17-19% m.c. wheat at 25°C increased while the germination percentages decreased with storage time. Germination dropped from 98 to 92-89% when the dry matter losses were about 0.05% and visible mould occurred when the dry matter losses were about 0.1% in 17-19% m.c. wheat.